Copyright in the Time of COVID-19: An Australian Perspective - Bellenger, Amanda; Balfour, Helen (Journal of Copyright in Education & Librarianship, 2021)
COVID-19 has raised many challenges in terms of applying Australian copyright legislation and related policies to higher education context. This paper describes the experience of Copyright Officers at Curtin University and Murdoch University from the initial stages of border-control measures affecting delivery of learning materials to students in China, to the wider disruption of the pandemic with many countries implementing lockdown measures, to the current environment where remote delivery is the “new normal.” The Australian Copyright Act 1968 (Commonwealth of Australia) provides narrow fair dealing exceptions (sections 40 and 41) and broader but more uncertain flexible dealing exceptions (section 200AB), creating a barrier for educators providing access to the information resources needed for teaching, learning, and research. The uncertainty of applying section 200AB was exacerbated by the conditions caused by the pandemic. The authors describe their experiences in providing copyright support during the pandemic as well as how the copyright services adapted to meet requirements.